2014
DOI: 10.1177/1054773814548508
|View full text |Cite
|
Sign up to set email alerts
|

Deciding to Seek Emergency Care for Acute Myocardial Infarction

Abstract: The purpose of this qualitative descriptive study was to explore how patients who experience acute myocardial infarction (AMI) decide to seek emergency care. Fifty patients with AMI were interviewed at two hospitals in Lebanon. The perspective of 22 witnesses of the attack was also sought about the cardiac event. The themes that transpired from the data were as follows: making sense of the symptoms, waiting to see what happens, deciding to come to the hospital, and the family influenced the decision to seek ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Waiting out of concern for cost of care is in line with the findings of Dumit, Noureddine, and Magilvy (2016). The fact that only 26% expressed financial concern in this study could be explained by It is worth noting that the participants' responses about what they would do if they experience a heart attack did not concur with the response strategies they reported in the qualitative study during their hospitalization (Noureddine, Dumit, & Saab, 2015). One example is the 24 participants (48%) who reported waiting for symptoms to go during the heart attack in the qualitative study versus only 10 participants (20%) who reported that they would wait to be sure before going to hospital in this study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Waiting out of concern for cost of care is in line with the findings of Dumit, Noureddine, and Magilvy (2016). The fact that only 26% expressed financial concern in this study could be explained by It is worth noting that the participants' responses about what they would do if they experience a heart attack did not concur with the response strategies they reported in the qualitative study during their hospitalization (Noureddine, Dumit, & Saab, 2015). One example is the 24 participants (48%) who reported waiting for symptoms to go during the heart attack in the qualitative study versus only 10 participants (20%) who reported that they would wait to be sure before going to hospital in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Inpatient and outpatient services must coordinate patient education. Family members need to be included, as most adults in Lebanon live with their families and healthcare decisions are often made in a collectivist manner, as transpired from the qualitative interviews done with this sample (Noureddine et al, ). Nevertheless, standard information giving is not enough.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with studies of cardiac patients in Lebanon that found that people often prefer driving to the hospital rather than waiting for an ambulance to come. [ 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the included studies were either Muslims or Christians. Five studies were conducted in Jordan (Al-Ali & Haddad, 2004;Al-Hassan & Wierenga, 2000;Elshatarat et al, 2013;Mosleh & Almalik, 2016;Mosleh & Darawad, 2015), four studies in Lebanon (Dumit, Magilvy, & Afifi, 2016;Dumit, Noureddine, & Magilvy, 2016;Noureddine et al, 2015;Walsh et al, 2017), one in Israel (Reges et al, 2013), one in Qatar (Donnelly et al, 2012) and one in Saudi Arabia (Al-Khadra et al, 1992), see online supplementary Appendix 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%